Anthropogenic heat due to energy consumption contributes to cooler and wetter summers in Southwest China - Zhang, Mengyi; Zhao, Jingchuan; Chen, Bing; Zheng, Yuhao; Lu, Mingwei; Wu, Xue; Yang, Huiyi; Liu, Xiaohong; Wu, Chenglai; Zhang, Meigen; Zhao, Xiaoqing; Jinlin, Zha; et al. (Frontiers in Earth Science, 2023)
Anthropogenic heat release (AHR) is the release of heat generated by anthropogenic energy consumption. AHR is geographically concentrated and fundamentally correlates with regional social economy and population. The regional mean AHR flux in Southwest China (SWC) grew quickly from 0.06 W m-2 in 1992 until it peaked at 0.37 W m-2 in 2019. In the urban regions, however, the flux of AHR exceeded 10 W m-2. This study examines the climatic effects and feedbacks of AHR due to energy consumption in SWC during the boreal summer using simulations from the Community Earth System Model (CESM). The modeling results show that AHR can impact large-scale atmospheric circulation in SWC, which transports more water vapor and consequently increases the humidity and low cloud cover in SWC. This effect impacts the energy balance at the surface by reducing the amount of incoming shortwave radiation that reaches the ground. AHR decreases the average 2-m air temperature in SWC by 0.10 °C, and decreases the minimum and maximum air temperatures in SWC as well. AHR contributes to cooler and wetter summers in SWC. The results show that AHR is a nonnegligible factor that impacts the climate of SWC. This study improves our understanding of the climate change caused by human activities in SWC.